Utilization of Waste Through Ecoliteration Approaches Based on High-Thinking Skill in Elementary School - Budiana, Deden Redy; Muharam, Agus; Hikamudin, Moch. Irfan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The problem of rubbish waste is still a frightening specter for people today, it is seen from the various adverse effects it causes. Starting from the problem of reducing, disposing, and even eliminating waste, to the adverse effects of disasters due to incorrect handling of waste. Basic and sustainable concrete solutions are needed. One of them is by habitualizing elementary school-age children to handle the waste problem more wisely. The purpose of this study is to explore the implementation of an ecoliteration approach that is combined with high-level thinking skills in handling waste among elementary school students. Students should not only focus on the subject matter in class, but the need for psychomotor habituation, especially in the use of waste. In this case, the process of utilizing waste is integrated into the subjects of Natural Sciences and Cultural Arts and Crafts